IFNB/interferon-β regulates autophagy via a MIR1-TBC1D15-RAB7 pathway. Issue 4 (2nd April 2020) - Ejlerskov, Patrick; Rubinsztein, David C.; Pocock, Roger
ABSTRACT: Loss of IFNB/interferon-β in mice causes a Parkinson disease-like phenotype where many features, including SNCA/α-synuclein and MAPT/tau accumulation, can be attributed to a late-stage block in autophagic flux. Recently, we identified a mechanism that can explain this phenotype. We found that IFNB induces expression of Mir1, a microRNA that can reduce the levels of TBC1D15, a RAB GTPase-activating protein. Induction of this pathway decreases RAB7 activity and thereby stimulates macroautophagy/autophagy. The relevance of these key players is deeply conserved from humans to Caenorhabditis elegans, highlighting the importance of this ancient autophagy regulatory pathway.